2022
DOI: 10.1093/neuonc/noac144
|View full text |Cite
|
Sign up to set email alerts
|

Trastuzumab deruxtecan in patients with central nervous system involvement from HER2-positive breast cancer: The DEBBRAH trial

Abstract: Background Trastuzumab deruxtecan (T-DXd) has shown durable antitumor activity in pretreated patients with HER2-positive advanced breast cancer (ABC), but its efficacy has not yet been evaluated in patients with active brain metastases (BMs). DEBBRAH aims to assess T-DXd in patients with HER2-positive or HER2-low ABC and central nervous system involvement. Methods This ongoing, five-cohort, phase II study (NCT04420598) enroll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
111
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(115 citation statements)
references
References 22 publications
2
111
0
2
Order By: Relevance
“…The phase 2 DEBBRAH trial evaluated trastuzumab deruxtecan in different cohorts of patients with breast cancer and central nervous system disease. Preliminary results indicated activity in patients with stable brain metastases at baseline and responses were observed in five of nine patients with brain metastases progressing after previous local therapy 32 . A multi-institutional retrospective analysis of 16 breast cancer brain metastases patients treated with trastuzumab deruxtecan reported responses in 6 of 9 patients with progressive brain metastases as well 33 .…”
Section: Discussionmentioning
confidence: 91%
“…The phase 2 DEBBRAH trial evaluated trastuzumab deruxtecan in different cohorts of patients with breast cancer and central nervous system disease. Preliminary results indicated activity in patients with stable brain metastases at baseline and responses were observed in five of nine patients with brain metastases progressing after previous local therapy 32 . A multi-institutional retrospective analysis of 16 breast cancer brain metastases patients treated with trastuzumab deruxtecan reported responses in 6 of 9 patients with progressive brain metastases as well 33 .…”
Section: Discussionmentioning
confidence: 91%
“…Our data have important implications for potential future BRM screening programs ( Table 4 ). In light of a high cumulative incidence of BRM and comparatively low risk of death, patients with ERBB2- positive MBC may be ideal candidates for BRM screening, particularly in the setting of systemic therapies with known CNS efficacy 31 , 32 , 39 , 40 , 41 and survival benefits that extend to patients with active BRM. 42 Further, given an almost linear increase in incidence of BRM for at least 5 years after a MBC diagnosis, ongoing long-term screening for intracranial metastatic disease may be indicated among patients with ERBB2- positive MBC.…”
Section: Discussionmentioning
confidence: 99%
“…Given the narrow scope of patients enrolled in clinical trials, the recently updated ASCO guidelines for management of HER2+ BCBM do not recommend trials of systemic therapy for newly diagnosed symptomatic BCBM [ 6 ]. In clinical trials that have included symptomatic patients, as well as in clinical experience, patients can have dramatic improvement in neurologic symptoms with HER2+ targeted systemic agents that have CNS activity ( Figure 1 ) [ 13 , 15 , 24 , 25 ]. There are no head-to-head comparisons of local therapy compared to systemic therapy making decisions in this rapidly evolving space complicated for patients and providers.…”
Section: Her2-targeted Systemic Agents With Data To Support Cns Activitymentioning
confidence: 99%
“…This study reported improvement in the ORR (79.7% in patients treated with T-DXd compared to 34.2% for T-DM1) and in 12-month PFS (75.8% for patients receiving T-DXd compared to 34.1% with T-DM1) [ 32 ]. This study allowed 82 patients with clinically stable, previously treated BCBM and found a mPFS of 15 months with T-DXd compared to 3 months with T-DM1 and stable BCBM in 23.8% of patients treated with T-DXd compared to 19.8% treated with T-DM1[ 13 ]. In no other study has the mPFS exceeded a year for patients with HER2+ BCBM ( Table 1 ).…”
Section: Her2-targeted Systemic Agents With Data To Support Cns Activitymentioning
confidence: 99%